Contribuição da atividade microbiana junto à serapilheira em um solo degradado do Bioma Caatinga - Cardoso, Francisco Moreira (2011)
The ecosystems of the Caatinga forest are currently on severe process of degradation, with the replacement of native plant species for crops and pastures. The plant litter includes the organic material laid on the soil coming from the native vegetation, which protects the soil by: reducing the temperature, increasing the percolation process, reducing the impact of rain drop and minimizing the losses caused by erosion; the litter decomposition isthe main processthrough which the nutrient can cycle in the ecosystems. The objective of this study was to evaluate, through the microbial and soil chemical changes, occurrence of soil degradation in areas of the Caatinga forest of Ceará where there was litter production. This research was conducted with the hypothesis that the litter produced by Caatinga forest is a potential source for the rehabilitation of degraded soil. The experiment was conducted in a degraded area in the General Sampaio county area, Ceará State, owned by Mr. Elias Andrade; the one year study received an initial contribution of litter which came from the Environmental Preservation Area (APA) - Elias Andrade. The APA was the area from where the entire litter was collected and corresponded to a 5 m x 5 m area and included four distinct sites, whose average of the litter total mass was 84 kg, which was taken as a quantitative reference treatment (100%), considered as the contribution from the degraded area. The other treatments were based on that value. The experimental design was randomized blocks (DBC) with the experimental arrangement in a split plot design (EPSSD), with 6 levels of litter (0%, 20%, 40%, 60%, 80%, 100%), two depths (0 -5 and 5-20 cm) and three seasons (february/2009, and september/2009 february/2010). The data collections involved both wet and dry season. Microbiological parameters were: Soil Basal Respiration (SBR), Microbial Biomass Carbon (MBC), Metabolic Quotient (qCO2) and Arbuscular Mycorrhizal Fungi (AMF). The chemical parameters were: nitrogen (N), phosphorus (P), Potassium (K), calcium (Ca), magnesium (Mg) contents and pH. The RBS had a higher concentration related to the rainy season, showing that during the dry season the microbial activity is reduced, and, consequently, the nutrition of the vegetation, via litter production, is compromised for the rehabilitation of the degraded areas. The highest levels of litter has positively contributed to: the elevation of the CBM, decrease of the qCO2 and increase of the spores AMF. The deposition of the litter contributed to the introduction of seeds and consequently for the establishment of native plants; however, the litter only partially modified the soil microbialogical attributes but not the chemical attributes, which will need both a medium and a long term evaluations.